Lunate dislocations: anatomy, diagnosis and management. (2nd July 2021) - Garner, Madeleine; Rudran, Branavan; Khan, Amir; Tang, Quen; Mathew, Philip
Abstract : Lunate dislocation is an uncommon but serious wrist injury, often resulting from a high energy mechanism of trauma. Advanced trauma life support protocols should be followed to diagnose and treat concomitant life-threatening pathology. Thorough neurovascular and soft tissue examination is required to identify open wounds and median nerve dysfunction, including acute onset carpal tunnel syndrome. Imaging is undertaken to appreciate injury severity, which is graded by the Mayfield classification. Closed reduction in the emergency department is the initial management, which alleviates pressure on neurovascular structures. Definitive management is surgical, most commonly via open reduction and direct ligamentous stabilisation. The aims of surgery are to restore anatomical carpal alignment and maintain stability, allowing repair and healing of the important wrist ligaments. Medium-to long-term functional outcomes are adequate, with most patients returning to work within 6 months. However, progressive radiographic midcarpal arthrosis is common, as well as permanent loss of grip strength, range of motion and chronic pain. This article considers the anatomy, diagnosis and management of acute lunate and perilunate dislocations.